Komunikasi Organisasi Pengurus Masjid An-Nur Asmil Surakarta yang Berbeda Ormas Islam dalam Menciptakan Hubungan Harmonis - Sihabuddin, Sihabuddin; Widiyowati, Estu; Qurrata A'yun, Ariza (Jurnal Ilmu Komunikasi, 2023)
This research aims to describe and analyze how organizational communication occurs between the administrators of the An-Nur Asmil Mosque in Surakarta to create harmonious relationships, even though the administrators have different backgrounds from Islamic groups or organizations. This research method uses a qualitative-descriptive research type. The research results show that: 1). The organizational communication of the administrators of the An-Nur Asmil Mosque in Surakarta is guided by the initial goals mutually agreed upon in the organizational rules; 2). The mosque administrators look for similarities in every difference and put aside personal egos and group names; 3). The communication process focuses on objectives in a way that listens to each other, understands each other, gives in to each other, and respects each other. In this way, harmonious organizational communication is created between the administrators of the An-Nur Asmil Mosque in Surakarta.